A BRIEF STUDY OF ERNEST HEMINGWAY’S THE OLD MAN AND THE SEA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The Old Man and the Sea is the high watermark of Hemingway’s thought and aesthetics and explores a new intensity as T.S. Eliot viewed it. The book won for the novelist three coveted awards, Pulitzer Prize in 1952, the Order of Carlos Manuel de Cespedes, the highest honour from the Cuban government in recognition of Hemingway’s long association with Cuba and her people and his glorification of a simple Cuban fisherman and finally it was instrumental in his being awarded the Nobel Prize 1955 (announced in 1954) which made the already famous author an international figure. This intensely vivid novel was received the entire world over as a mini epic done on a splendid design.